Incidence of Cervical Spine Injuries Among Patients with Maxillofacial Trauma - Sonia Mubeen, Maria Rasheed, Saddique Aslam Khattak, Khurram Nadeem, Muhammad Mohsin Tahir, Ikram Manzoor (Pakistan Journal of Medical & Health Sciences, 2023)
A substantial portion of cervical spine injuries occurs due to maxillofacial trauma. A delay in the identification of cervical injuries can result in major neurological issues, paralysis, and even death. Therefore, early detection of cervical fractures in patients with maxillofacial trauma is crucial. Aim: The goal of the study is to assess the incidence of cervico-spinal injuries in patients with oral and maxillofacial trauma. Methods: This cross-sectional study was carried out at the Oral and Maxillofacial Surgery department of Mayo Hospital, Lahore for the duration of one year from January 2021 to January 2022. A total of 120 maxillofacial trauma patients treated at the oral surgery department. By using computed tomography, lateral and anteroposterior X-rays; all patients were evaluated for cervical spine injuries. The dependent and independent variables’ information was gathered using a structured questionnaire. Results: In 4 (3.3%) patients, cervical spine and maxillofacial injuries were found. Six males and two women were involved in the ten Cervical-spine injuries. The ratio of men to women was 4:1. Despite the low frequency of cervical injuries related with maxillofacial fractures, suitable and precise recommendations for the diagnosis and treatment of these cervical injuries must be adopted to avoid permanent disability and even death. Keywords: Frequency, Maxillofacial trauma, Cervical spine injury